2018
DOI: 10.1111/jpi.12464
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic supplement with melatonin successfully suppresses the pathogenesis of periodontitis through normalizing RANKL/OPG ratio and depressing the TLR4/MyD88 signaling pathway

Abstract: Periodontitis (PD) is an inflammatory disease characterized by gingival inflammation and resorption of alveolar bone. Impaired receptor activator of nuclear factor-kappa B ligand/osteoprotegerin (RANKL/OPG) signaling caused by enhanced production of pro-inflammatory cytokines plays an essential role in the pathogenesis of PD. Considering melatonin possesses significant anti-inflammatory property, this study aimed to determine whether prophylactic treatment with melatonin would effectively normalize RANKL/OPG s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 65 publications
4
49
0
Order By: Relevance
“…As the proinflammatory actions of TLR4 are frequently also associated with NF‐κB activation and prooxidant effects, inhibitory actions of melatonin on TLR4 are of particular mechanistic interest for the understanding of reducing inflammation. This mode of action by melatonin was repeatedly demonstrated and sometimes shown to be associated with inhibitions of NF‐κB and of inflammasome activation as well as upregulation of Nrf2 . These findings were obtained in different organs and models, under various conditions, from endotoxemia, ischemia/reperfusion and other forms of brain injury to chemically induced inflammation.…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 79%
“…As the proinflammatory actions of TLR4 are frequently also associated with NF‐κB activation and prooxidant effects, inhibitory actions of melatonin on TLR4 are of particular mechanistic interest for the understanding of reducing inflammation. This mode of action by melatonin was repeatedly demonstrated and sometimes shown to be associated with inhibitions of NF‐κB and of inflammasome activation as well as upregulation of Nrf2 . These findings were obtained in different organs and models, under various conditions, from endotoxemia, ischemia/reperfusion and other forms of brain injury to chemically induced inflammation.…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 79%
“…Given normal physiologic conditions, the colon does not express Reg3β and α-defensin but these AMPs are induced in colitis 55 , suggesting that TLR4 signalling www.nature.com/scientificreports www.nature.com/scientificreports/ also plays a role in Reg3β regulation by melatonin. Although melatonin has been reported to inhibit TLR4/NF-κB signalling 56,57 , TLR4 signalling appears to link pathogen sensing and AMP production is thought to play protective role in melatonin function. Experiments with TLR4 KO mice and TLR4 inhibitor revealed the anti-colitic effects of melatonin on goblet cell differentiation and induction of melatonin receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the RANKL/osteoprotegerin ratio, Toll‐like receptor (TLR)4/MyD88 activity, and pro‐inflammatory cytokine levels were imbalanced following periodontitis. However, in melatonin‐pretreated rats, all of these parameters were successfully restored to nearly normal levels with the maximal dose (100 mg/kg), which suggests that melatonin may counteract periodontitis‐induced destructive bone damage . Melatonin treatment reduces serum levels of terminal C telopeptide of collagen Type I (CTX), RANKL, and osteoclast activity but increases bone ALP in an experimental periodontitis rat model.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…However, in melatonin-pretreated rats, all of these parameters were successfully restored to nearly normal levels with the maximal dose (100 mg/kg), which suggests that melatonin may counteract periodontitis-induced destructive bone damage. 133 Melatonin treatment reduces serum levels of terminal C telopeptide of collagen Type I (CTX), RANKL, and osteoclast activity but increases bone ALP in an experimental periodontitis rat model. The results revealed that melatonin treatment significantly inhibits regional resorption of alveolar bone and contributes to periodontal healing in this experimental periodontitis rat model.…”
Section: Prospects and Conclusionmentioning
confidence: 99%